2018
DOI: 10.14701/ahbps.2018.22.4.397
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of post-operative drain amylase levels for post-operative pancreatic fistula

Abstract: Backgrounds/AimsTraditionally, surgically placed pancreatic drains are removed, at the discretion of the operating surgeon. Moving towards enhanced recovery after surgery (ERAS), we looked for predictors for early drain removal. The purpose of this paper was to establish which postoperative days' (POD) drain amylase is most predictive against post-operative pancreatic fistula (POPF).MethodsWe conducted a retrospective study of 196 patients who underwent pancreatic resection at our institute from January 2006 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…A recovery rate of injected fluid > 80% should be guaranteed; and (3) Toxic amylase levels should decrease dramatically after CLL. Amylase levels in the drainage discharge are extremely important to evaluate pancreatic leakage after surgery[22]. Amylase levels in the draining discharge within the lower triple-digits ( i.e ., approximately 100–500 U/L) are ideal after CLL induction.…”
Section: Discussionmentioning
confidence: 99%
“…A recovery rate of injected fluid > 80% should be guaranteed; and (3) Toxic amylase levels should decrease dramatically after CLL. Amylase levels in the drainage discharge are extremely important to evaluate pancreatic leakage after surgery[22]. Amylase levels in the draining discharge within the lower triple-digits ( i.e ., approximately 100–500 U/L) are ideal after CLL induction.…”
Section: Discussionmentioning
confidence: 99%
“…POD #3 was selected given prior reports in which drain amylase was used as an indicator of safety for drain removal at this time point . 2 , 8 …”
Section: Methodsmentioning
confidence: 99%
“…Reported rates of POPF range from 3-45%, with a 0-5% mortality rate. 1 - 4 A systematic review of 60,000 patients demonstrated that 3.5% of all pancreaticoduodenectomy patients had a POPF that lead to organ failure, the need for re-operation, or death. An additional 8.9% of patients required antibiotic therapy or additional procedures such as percutaneous, endoscopic, or angiographic interventions as part of their POPF treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations